Mucinous Eccrine Carcinoma of the Eyelid: A Case Report Study - Etrat Javadirad; Javad Azimivaghar; Saba Montazer (Babol University of Medical Sciences, 2020)
Background: Primary mucinous eccrine carcinoma (PMEC) is a quite rare malignant tumor that typically involves the head and neck region in approximately 75% of patients and the periorbital area is the most common area. Case Presentation: A 57-year-old man was seen with a painless red mass involving the left lower eyelid for the past 7 months. Examination revealed a small mass measuring 0.6 cm with shiny red smooth appearance of the skin. H&E stained examination revealed a tumor mass that composed of polygonal cells in nests, lobules and islands separated by large amount of mucin. The neoplastic cells showed eosinophilic cytoplasm and round nuclei with mild pleomorphism. There was no necrosis, no atypical mitosis, no lymphovascular and perineural invasion. Rare mitotic figures were found. Tumoral nests present on all surgical margins. Primary MEC is a slow-growing neoplasm that may recur after incomplete surgical excision. This tumor is often clinically mistaken for other cutaneous tumors due to its variable appearance. Recurrent tumor tends to be locally invasive with a rare metastatic rate of 9.6%. Conclusion: As a result of the recurrence risk, patients should be followed up regularly. Thus, our patient was recommended to have a regular follow-up every six months.